2010
DOI: 10.1289/ehp.0901435
|View full text |Cite
|
Sign up to set email alerts
|

Polybrominated Diphenyl Ethers Induce Developmental Neurotoxicity in a Human in Vitro Model: Evidence for Endocrine Disruption

Abstract: BackgroundPolybrominated diphenyl ethers (PBDEs) are persistent and bioaccumulative flame retardants, which are found in rising concentrations in human tissues. They are of concern for human health because animal studies have shown that they possess the potential to be developmentally neurotoxic.ObjectiveBecause there is little knowledge of the effects of PBDEs on human brain cells, we investigated their toxic potential for human neural development in vitro. Moreover, we studied the involvement of thyroid horm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
139
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 189 publications
(145 citation statements)
references
References 61 publications
6
139
0
Order By: Relevance
“…Cytotoxicity as measured by MTT reduction was detected in the neuroblastoma cell line SK-N-MC (Tagliaferri et al, 2010) and the human astrocytoma cell line (132-1N1) (Madia et al, 2004). In addition, alterations in neural migration/differentiation of human neural progenitor cells (Schreiber et al, 2010) and modulations of calcium uptake determined in rat mitochondria (Coburn et al, 2008) have been reported. Large-scale proteomic analyses with non-toxic and cytotoxic concentrations showed that BDE-99 alters the expression of cytoskeletal proteins already at low concentrations in cerebellar cortical cells isolated from rat fetuses on GD21 (Sprague-Dawley rats).…”
Section: Neurotoxicitymentioning
confidence: 99%
“…Cytotoxicity as measured by MTT reduction was detected in the neuroblastoma cell line SK-N-MC (Tagliaferri et al, 2010) and the human astrocytoma cell line (132-1N1) (Madia et al, 2004). In addition, alterations in neural migration/differentiation of human neural progenitor cells (Schreiber et al, 2010) and modulations of calcium uptake determined in rat mitochondria (Coburn et al, 2008) have been reported. Large-scale proteomic analyses with non-toxic and cytotoxic concentrations showed that BDE-99 alters the expression of cytoskeletal proteins already at low concentrations in cerebellar cortical cells isolated from rat fetuses on GD21 (Sprague-Dawley rats).…”
Section: Neurotoxicitymentioning
confidence: 99%
“…they may then, e.g., be used for electrophysiological studies or to follow differentiation during radial migration on a laminin-coated surface (Moors et al, 2007(Moors et al, , 2009van Vliet et al, 2007). It is noteworthy that despite differentiation onto a surface, this manner of differentiation differs from simple 2D single cell plating because there is glial cell guidance with neuronal growth on top in a processorganized manner out of an organoid cell system (Ahlenius and Kokaia, 2010;Bal-Price et al, 2012;liu and Sun, 2011;Schreiber et al, 2010). this phenomenon can be seen in the organized process of cell migration, which can also be quantified in such a system (Moors et al, 2007(Moors et al, , 2009.…”
Section: Issues and Future Challenges To Be Addressed By 3d In Vitro mentioning
confidence: 99%
“…Mouse neural progenitor cells (mNPCs) can be prepared from embryonic or postnatal mouse pup brains of different ages. Such progenitors grow as neurospheres, develop in vitro, and are especially valuable as a source of genetically manipulated primary cells (Gassmann et al, 2010). Human cell systems are recommended as the most relevant in the context of the 21 st century approach in toxicity testing: getting a better prediction of human toxicity by using human in vitro models (NRC 2007).…”
Section: Clinical Perspectives Of Developmental Neurotoxicitymentioning
confidence: 99%